Synthesis and Antimicrobial Properties of New Derivatives of Morpholine and Piperidine Based on 1-Chloro-3-methoxy-propylbenzene - Duruskari, G.Sh.; Maharramov, M.N.; Hasanova, U.Sh.; Ganbarov, Kh.G.; Eyvazova, G.M.; Israyilova, A.A.; Maharramov, A.M. (Asian Journal of Chemistry, 2017)
The compounds 1-(3-methoxy-1-phenyl-propyl)morpholine and 1-(3-methoxy-1-phenyl-propyl) piperidine have been synthesized using (3-methoxy-propenyl)benzene and 1-chloro-3-methoxy-propylbenzene. The structures of the synthesized compounds were analyzed by NMR and IR spectroscopic methods. Biological activities of obtained products were investigated against Gram-negative and Gram-positive microorganisms. It has been showed that all the synthesized compounds possess pronounced antimicrobial activity against pathogenic bacteria Acinetobacter baumannii BDU32, Escherichia coli BDU12, Klebsiella pneumoniae BDU44, Pseudomonas aeruginosa BDU49 and Staphylococcus aureus BDU23.